Catalyst for producing aromatic polycarboxylic acid through liquid phase oxidation and application of catalyst

By using catalysts containing Co, Mn, IVB salts, hydroxycarboxylates and bromine compounds in CTA production, the problem of high metal impurities content in CTA is solved, and the effect of improving product selectivity and reducing metal impurities content is achieved.

CN119488950AActive Publication Date: 2025-02-21CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311034279.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-16
Publication Date
2025-02-21
Estimated Expiration
2043-08-16

AI Technical Summary

Technical Problem

In the prior art, the metal impurities content in crude terephthalic acid (CTA) products is high, which affects product quality and subsequent polymerization of polyester.

Method used

Provide a catalyst for liquid phase oxidation to produce aromatic polycarboxylic acids, including Co salts, Mn salts, IVB salts, hydroxycarboxylates and bromine-containing compounds. By optimizing component ratios and reaction conditions, the selectivity of CTA is improved and the selectivity of CTA is reduced. Metal impurities content.

Benefits of technology

It significantly reduces the content of metal impurities such as Co and Mn in CTA products, improves product selectivity and quality, and reduces the generation of by-products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004398476450000091
    Figure BDA0004398476450000091
  • Figure BDA0004398476450000101
    Figure BDA0004398476450000101
Patent Text Reader

Abstract

The invention discloses a catalyst for producing aromatic polycarboxylic acid through liquid-phase oxidation and application of the catalyst. The catalyst comprises Co salt, Mn salt, IVB group salt, hydroxy carboxylate and a bromine-containing compound, the weight ratio of Co to Mn to IVB group elements to hydroxy carboxylate to Br is 500: (200 to 300): (5 to 20): (10 to 50): (500 to 2000). When the catalyst provided by the invention is used for producing aromatic polycarboxylic acid through liquid phase oxidation, the catalyst has the characteristics of reducing the content of metal impurities in a CTA product and improving the selectivity of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts, and in particular relates to a catalyst for producing aromatic polycarboxylic acids by liquid phase oxidation and application thereof. Background Art

[0002] Crude terephthalic acid (CTA) can be hydrorefined to produce purified terephthalic acid (PTA), a basic raw material for the synthesis of polyethylene terephthalate (PET). Demand for PTA continues to grow, with global PTA demand projected to reach 100 million tons by 2023. Currently, the primary production technology for PTA is a two-step process developed by Amoco-MC involving the oxidation of para-xylene (PX) and hydrorefining. The oxidation step utilizes a Co-Mn-Br catalyst system and acetic acid as the solvent. The hydrogenation step primarily converts para-formylbenzoic acid (4-CBA) to para-toluic acid (p-TA), which is then removed by centrifugation and water washing.

[0003] In the synthesis of terephthalic acid (PTA), the homogeneous catalysts used contain metal components, such as Co and Mn. These components can weakly interact with the terephthalic acid product, leading to metal residues in the PTA product. This can reduce product quality and darken the color, seriously impacting subsequent polyester polymerization and product quality. Currently, the industry addresses this issue by increasing the number of washes and wash ratios, which results in increased energy consumption. For example, in the oxidation process disclosed in US Pat. No. 7,985,875 B2 (Process for preparing aromatic polycarboxylic acid by liquid phase oxidation), despite multiple separations, the Co and Mn contents in CTA remain high. Summary of the Invention

[0004] To address the technical problem of high metal content in crude terephthalic acid (CTA) products produced by oxidation in existing technologies, the present invention provides a catalyst for producing aromatic polycarboxylic acids through liquid-phase oxidation and its application. The catalyst provided by the present invention reduces the metal impurity content of the CTA product and improves product selectivity.

[0005] The first aspect of the present invention provides a catalyst for producing aromatic polycarboxylic acids by liquid-phase oxidation, comprising a Co salt, a Mn salt, a Group IVB salt, a hydroxycarboxylate, and a bromine-containing compound; in terms of weight, the ratio of Co:Mn:Group IVB element:hydroxycarboxylate:Br is 500:(200-300):(5-20):(10-50):(500-2000).

[0006] Furthermore, the Co salt is cobalt acetate.

[0007] Furthermore, the Mn salt is manganese acetate.

[0008] Furthermore, the Group IVB salt is at least one of zirconium acetate or hafnium acetate, preferably zirconium acetate and hafnium acetate.

[0009] Furthermore, the hydroxycarboxylate is at least one of tartrate, heptanoate, gluconate, and alginate, preferably tartrate. Furthermore, the hydroxycarboxylate is potassium salt, sodium salt, or potassium sodium salt.

[0010] Furthermore, the bromine-containing compound is selected from at least one of inorganic bromides and brominated hydrocarbons.

[0011] Furthermore, the inorganic bromide is selected from hydrogen bromide or alkali metal bromide.

[0012] Furthermore, the bromohydrocarbon is selected from at least one of tetrabromoethane, tetrabromopropane, and tetrabromobutane. The specific substitution position of the bromine in the bromohydrocarbon is not particularly limited. The bromohydrocarbon is, for example, but not limited to, at least one selected from 1,1,2,2-tetrabromoethane, 1,1,1,2-tetrabromoethane, 1,1,2,2-tetrabromopropane, and 2,2,3,3-tetrabromobutane.

[0013] Furthermore, in the catalyst, when Co is 500 parts by weight, the weight parts of the IVB group element can be selected from one of 210, 220, 230, 240, 250, 260, 270, 280, and 290, the weight parts of the hydroxycarboxylate can be selected from one of 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, and 19, and the weight parts of Br can be selected from one of 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, and 1900.

[0014] The second aspect of the present invention provides a method for producing aromatic polycarboxylic acids by liquid phase oxidation, which comprises using acetic acid as a solvent and reacting polyalkyl-substituted aromatic hydrocarbons with an oxidant in the presence of the catalyst provided in the first aspect to obtain aromatic polycarboxylic acids.

[0015] Furthermore, the oxidant is a gas containing elemental oxygen, such as but not limited to oxygen, air, an oxygen-nitrogen mixture, an oxygen-air mixture, an oxygen-nitrogen mixture, and the like.

[0016] Furthermore, the aromatic hydrocarbon in the polyalkyl-substituted aromatic hydrocarbon is preferably benzene or naphthalene.

[0017] Furthermore, the polyalkyl-substituted aromatic hydrocarbon is preferably a dialkyl-substituted aromatic hydrocarbon.

[0018] Furthermore, the alkyl group in the polyalkyl-substituted aromatic hydrocarbon is preferably a C1-C4 alkyl group, such as but not limited to a methyl group, an ethyl group or a propyl group.

[0019] Furthermore, the polyalkyl aromatic hydrocarbons are exemplified but not limited to p-xylene and m-xylene.

[0020] Furthermore, the reaction temperature is preferably 160-250°C.

[0021] Furthermore, the reaction pressure is preferably 0.8-2.0 MPa.

[0022] Furthermore, the reaction time is preferably 1 to 5 hours.

[0023] Furthermore, the oxidant of the reaction is preferably air, and the space velocity (the ratio of the volume flow rate of gas to the volume of the liquid raw material mixture) is 2 to 5 h -1 .

[0024] Furthermore, in the reaction, the mass ratio of the polyalkyl substituted aromatic hydrocarbon, the solvent, and the catalyst is 1:(2-10):(1×10 -4 ~1×10 -3 ).

[0025] Furthermore, the crude terephthalic acid (CTA) obtained by the reaction can be hydrogenated to obtain purified terephthalic acid (PTA).

[0026] Furthermore, the mass content of Co in the crude terephthalic acid (CTA) obtained by the reaction does not exceed 1 ppmw, and is more preferably less than 0.8 ppmw; the mass content of Mn does not exceed 1.5 ppmw, and is preferably less than 0.9 ppmw.

[0027] It is easy for those skilled in the art to understand that the number of alkyl groups in the aromatic polycarboxylic acid obtained by the above method is the same as the number of alkyl groups in the polyalkyl-substituted aromatic hydrocarbon molecules used.

[0028] Compared with the prior art, the present invention can produce the following beneficial effects:

[0029] Conventional liquid-phase oxidation catalysts for producing aromatic polycarboxylic acids in the art have weak interactions between Co and Mn salts and the terephthalic acid product, resulting in residual metal components in the PTA product. The present invention provides a liquid-phase oxidation catalyst for producing aromatic polycarboxylic acids, comprising a Co salt, a Mn salt, a Group IVB salt, a hydroxycarboxylate, and a bromine-containing compound. By utilizing the interaction of these components, the catalyst improves the selectivity of crude terephthalic acid (CTA), reduces the production of byproducts 4-CBA and p-TA, and significantly reduces the content of metal impurities (Co salts, Mn salts, and Group IVB salts) in the CTA product, particularly achieving a Co content of less than 0.8 ppmw and a Mn content of less than 0.9 ppmw, both of which are significantly lower than the metal impurities found in prior art products. DETAILED DESCRIPTION

[0030] The following examples will further illustrate the technical solutions provided by the present invention, but the protection scope of the present invention is not limited to these examples.

[0031] For the products of the embodiments of the present invention and the comparative examples, the samples to be analyzed were first completely dissolved in dimethyl sulfoxide, and PX was analyzed by gas chromatography, while the other substances were analyzed by high performance liquid chromatography (HPLC).

[0032] [Example 1]

[0033] The reaction was carried out in a 1000 ml titanium autoclave equipped with a magnetic stirrer, gas delivery line, reflux condenser, thermocouple, and rupture disc. The stirring speed was 400 rpm and the reaction was heated by circulating hot oil. The reaction steps were as follows:

[0034] 1) Weigh 80g of p-xylene, 400g of acetic acid, 20g of metal acetate (based on the entire solution, containing 500ppmwCo 2+ 、250ppmw Mn 2+ 、15ppmwZr 4+ ), 0.44 g of 1,1,2,2-tetrabromoethane (the bromine content is 800 ppmw based on the entire solution), and 0.10 g of potassium sodium tartrate were mixed evenly and added into the autoclave, which was then sealed.

[0035] 2) Add 2.0MPa nitrogen and conduct an airtightness test for 30 minutes. The test is qualified if the pressure drop is no more than 0.1MPa within 30 minutes.

[0036] 3) Add nitrogen with a space velocity of 4h -1 , and start the stirrer at a stirring rate of 400 rpm, raise the temperature to 186°C, and maintain the pressure at 1.0 MPa.

[0037] 4) Switch to air at 186℃, air velocity is 4h -1, keep the temperature constant and react for 120 minutes.

[0038] 5) After the reaction is complete, switch to nitrogen again, cool to room temperature, depressurize the reactor to normal pressure, vacuum filter the oxidation product, wash the filtered solid with 1000 ml of pure water, and then continue to filter the washed solid. The obtained solid is dried in an oven at 130° C. for 8 h, cooled to room temperature in a dryer, and the solid sample is analyzed for organic impurities and metal impurities.

[0039] The tail gas was analyzed online using infrared, and the tail oxygen content was controlled between 3 and 6 wt%, and the CO2 content was controlled between 1.0 and 1.5 wt%. The catalyst formula is shown in Table 1, and the analysis results of the main impurities in the product are shown in Table 2.

[0040] [Example 2]

[0041] The reaction was carried out in a 1000 ml titanium autoclave equipped with a magnetic stirrer, gas delivery line, reflux condenser, thermocouple, and rupture disc. The stirring speed was 400 rpm and the reaction was heated by circulating hot oil. The reaction steps were as follows:

[0042] 1) Weigh 80g of p-xylene, 400g of acetic acid, 20g of metal acetate (based on the entire solution, containing 500ppmwCo 2+ 、250ppmw Mn 2+ 、15ppmw Hf 4+ ), 0.44 g of 1,1,2,2-tetrabromoethane (the bromine content is 800 ppmw based on the entire solution), and 0.10 g of potassium sodium tartrate were mixed evenly and added into the autoclave, which was then sealed.

[0043] 2) Add 2.0MPa nitrogen and conduct an airtightness test for 30 minutes. The test is qualified if the pressure drop is no more than 0.1MPa within 30 minutes.

[0044] 3) Add nitrogen with a space velocity of 4h -1 , and start the stirrer at a stirring rate of 400 rpm, raise the temperature to 186°C, and maintain the pressure at 1.0 MPa.

[0045] 4) Switch to air at 186℃, air velocity is 4h -1 , keep the temperature constant and react for 120 minutes.

[0046] 5) After the reaction is complete, switch to nitrogen again, cool to room temperature, depressurize the reactor to normal pressure, vacuum filter the oxidation product, wash the filtered solid with 1000 ml of pure water, and then continue to filter the washed solid. The obtained solid is dried in an oven at 130° C. for 8 h, cooled to room temperature in a dryer, and the solid sample is analyzed for organic impurities and metal impurities.

[0047] The tail gas was analyzed online using infrared, and the tail oxygen content was controlled between 3 and 6 wt%, and the CO2 content was controlled between 1.0 and 1.5 wt%. The catalyst formula is shown in Table 1, and the analysis results of the main impurities in the product are shown in Table 2.

[0048] [Example 3]

[0049] The reaction was carried out in a 1000 ml titanium autoclave equipped with a magnetic stirrer, gas delivery line, reflux condenser, thermocouple, and rupture disc. The stirring speed was 400 rpm and the reaction was heated by circulating hot oil. The reaction steps were as follows:

[0050] 1) Weigh 80g of p-xylene, 400g of acetic acid, 20g of metal acetate (based on the entire solution, containing 500ppmwCo 2+ 、250ppmw Mn 2+ 、7.5ppmwZr 4+ 、7.5ppmw Hf 4+ ), 0.44 g of 1,1,2,2-tetrabromoethane (the bromine content is 800 ppmw based on the entire solution), and 0.10 g of potassium sodium tartrate were mixed evenly and added into the autoclave, which was then sealed.

[0051] 2) Add 2.0MPa nitrogen and conduct an airtightness test for 30 minutes. The test is qualified if the pressure drop is no more than 0.1MPa within 30 minutes.

[0052] 3) Add nitrogen with a space velocity of 4h -1 , and start the stirrer at a stirring rate of 400 rpm, raise the temperature to 186°C, and maintain the pressure at 1.0 MPa.

[0053] 4) Switch to air at 186℃, air velocity is 4h -1 , keep the temperature constant and react for 120 minutes.

[0054] 5) After the reaction is complete, switch to nitrogen again, cool to room temperature, depressurize the reactor to normal pressure, vacuum filter the oxidation product, wash the filtered solid with 1000 ml of pure water, and then continue to filter the washed solid. The obtained solid is dried in an oven at 130° C. for 8 h, cooled to room temperature in a dryer, and the solid sample is analyzed for organic impurities and metal impurities.

[0055] The tail gas was analyzed online using infrared, and the tail oxygen content was controlled between 3 and 6 wt%, and the CO2 content was controlled between 1.0 and 1.5 wt%. The catalyst formula is shown in Table 1, and the analysis results of the main impurities in the product are shown in Table 2.

[0056] [Example 4]

[0057] The reaction was carried out in a 1000 ml titanium autoclave equipped with a magnetic stirrer, gas delivery line, reflux condenser, thermocouple, and rupture disc. The stirring speed was 400 rpm and the reaction was heated by circulating hot oil. The reaction steps were as follows:

[0058] 1) Weigh 80g of p-xylene, 400g of acetic acid, 20g of metal acetate (based on the entire solution, containing 500ppmwCo 2+ 、250ppmw Mn 2+ 、15ppmwZr 4+ ), 0.55 g of 1,1,2,2-tetrabromoethane (the bromine content is 1000 ppmw based on the entire solution), and 0.10 g of potassium sodium tartrate were mixed evenly and added into the autoclave, which was then sealed.

[0059] 2) Add 2.0MPa nitrogen and conduct an airtightness test for 30 minutes. The test is qualified if the pressure drop is no more than 0.1MPa within 30 minutes.

[0060] 3) Add nitrogen with a space velocity of 4h -1 , and start the stirrer at a stirring rate of 400 rpm, raise the temperature to 186°C, and maintain the pressure at 1.0 MPa.

[0061] 4) Switch to air at 186℃, air velocity is 4h -1 , keep the temperature constant and react for 120 minutes.

[0062] 5) After the reaction is complete, switch to nitrogen again, cool to room temperature, depressurize the reactor to normal pressure, vacuum filter the oxidation product, wash the filtered solid with 1000 ml of pure water, and then continue to filter the washed solid. The obtained solid is dried in an oven at 130° C. for 8 h, cooled to room temperature in a dryer, and the solid sample is analyzed for organic impurities and metal impurities.

[0063] The tail gas was analyzed online using infrared, and the tail oxygen content was controlled between 3 and 6 wt%, and the CO2 content was controlled between 1.0 and 1.5 wt%. The catalyst formula is shown in Table 1, and the analysis results of the main impurities in the product are shown in Table 2.

[0064] [Example 5]

[0065] The reaction was carried out in a 1000 ml titanium autoclave equipped with a magnetic stirrer, gas delivery line, reflux condenser, thermocouple, and rupture disc. The stirring speed was 400 rpm and the reaction was heated by circulating hot oil. The reaction steps were as follows:

[0066] 1) Weigh 80g of p-xylene, 400g of acetic acid, 20g of metal acetate (based on the entire solution, containing 500ppmwCo 2+ 、250ppmw Mn 2+、15ppmwZr 4+ ), 0.44 g 1,1,2,2-tetrabromoethane (the bromine content is 800 ppmw based on the entire solution), and 0.10 g sodium heptonic acid were mixed evenly and added into the autoclave, which was then sealed.

[0067] 2) Add 2.0MPa nitrogen and conduct an airtightness test for 30 minutes. The test is qualified if the pressure drop is no more than 0.1MPa within 30 minutes.

[0068] 3) Add nitrogen with a space velocity of 4h -1 , and start the stirrer at a stirring rate of 400 rpm, raise the temperature to 186°C, and maintain the pressure at 1.0 MPa.

[0069] 4) Switch to air at 186℃, air velocity is 4h -1 , keep the temperature constant and react for 120 minutes.

[0070] 5) After the reaction is complete, switch to nitrogen again, cool to room temperature, depressurize the reactor to normal pressure, vacuum filter the oxidation product, wash the filtered solid with 1000 ml of pure water, and then continue to filter the washed solid. The obtained solid is dried in an oven at 130° C. for 8 h, cooled to room temperature in a dryer, and the solid sample is analyzed for organic impurities and metal impurities.

[0071] 6) The tail gas is analyzed by infrared online, and the tail oxygen content is controlled between 3 and 6 wt%, and the CO2 content is controlled between 1.0 and 1.5 wt%.

[0072] The catalyst formula is shown in Table 1, and the main impurity analysis results in the product are shown in Table 2.

[0073] [Example 6]

[0074] The reaction was carried out in a 1000 ml titanium autoclave equipped with a magnetic stirrer, gas delivery line, reflux condenser, thermocouple, and rupture disc. The stirring speed was 400 rpm and the reaction was heated by circulating hot oil. The reaction steps were as follows:

[0075] 1) Weigh 80g of p-xylene, 400g of acetic acid, 20g of metal acetate (based on the entire solution, containing 500ppmwCo 2+ 、300ppmw Mn 2+ 、15ppmwZr 4+ ), 0.44 g of 1,1,2,2-tetrabromoethane (the bromine content is 800 ppmw based on the entire solution), and 0.10 g of potassium sodium tartrate were mixed evenly, added into the autoclave, and sealed.

[0076] 2) Add 2.0MPa nitrogen and conduct an airtightness test for 30 minutes. The test is qualified if the pressure drop is no more than 0.1MPa within 30 minutes.

[0077] 3) Add nitrogen with a space velocity of 4h -1 , and start the stirrer at a stirring rate of 400 rpm, raise the temperature to 186°C, and maintain the pressure at 1.0 MPa.

[0078] 4) Switch to air at 186℃, air velocity is 4h -1 , keep the temperature constant and react for 120 minutes.

[0079] 5) After the reaction is complete, switch to nitrogen again, cool to room temperature, depressurize the reactor to normal pressure, vacuum filter the oxidation product, wash the filtered solid with 1000 ml of pure water, and then continue to filter the washed solid. The obtained solid is dried in an oven at 130° C. for 8 h, cooled to room temperature in a dryer, and the solid sample is analyzed for organic impurities and metal impurities.

[0080] The tail gas was analyzed online using infrared, and the tail oxygen content was controlled between 3 and 6 wt%, and the CO2 content was controlled between 1.0 and 1.5 wt%. The catalyst formula is shown in Table 1, and the analysis results of the main impurities in the product are shown in Table 2.

[0081] [Example 7]

[0082] The reaction was carried out in a 1000 ml titanium autoclave equipped with a magnetic stirrer, gas delivery line, reflux condenser, thermocouple, and rupture disc. The stirring speed was 400 rpm and the reaction was heated by circulating hot oil. The reaction steps were as follows:

[0083] 1) Weigh 80g of p-xylene, 400g of acetic acid, 20g of metal acetate (based on the entire solution, containing 500ppmwCo 2+ 、250ppmw Mn 2+ 、15ppmwZr 4+ ), 0.44 g of 1,1,2,2-tetrabromoethane (the bromine content is 800 ppmw based on the entire solution), and 0.05 g of potassium sodium tartrate were mixed evenly and added into the autoclave, which was then sealed.

[0084] 2) Add 2.0MPa nitrogen and conduct an airtightness test for 30 minutes. The test is qualified if the pressure drop is no more than 0.1MPa within 30 minutes.

[0085] 3) Add nitrogen with a space velocity of 4h -1 , and start the stirrer at a stirring rate of 400 rpm, raise the temperature to 186°C, and maintain the pressure at 1.0 MPa.

[0086] 4) Switch to air at 186℃, air velocity is 4h -1 , keep the temperature constant and react for 120 minutes.

[0087] 5) After the reaction is complete, switch to nitrogen again, cool to room temperature, depressurize the reactor to normal pressure, vacuum filter the oxidation product, wash the filtered solid with 1000 ml of pure water, and then continue to filter the washed solid. The obtained solid is dried in an oven at 130° C. for 8 h, cooled to room temperature in a dryer, and the solid sample is analyzed for organic impurities and metal impurities.

[0088] The tail gas was analyzed online using infrared, and the tail oxygen content was controlled between 3 and 6 wt%, and the CO2 content was controlled between 1.0 and 1.5 wt%. The catalyst formula is shown in Table 1, and the analysis results of the main impurities in the product are shown in Table 2.

[0089] [Comparative Example 1]

[0090] The reaction was carried out in a 1000 ml titanium autoclave equipped with a magnetic stirrer, gas delivery line, reflux condenser, thermocouple, and rupture disc. The stirring speed was 400 rpm and the reaction was heated by circulating hot oil. The reaction steps were as follows:

[0091] 1) Weigh 80g of p-xylene, 400g of acetic acid, 20g of metal acetate (based on the entire solution, containing 500ppmwCo 2+ 、250ppmw Mn 2+ . ) and 0.44 g of 1,1,2,2-tetrabromoethane (the bromine content is 800 ppmw based on the entire solution), mixed well, added into the autoclave, and sealed.

[0092] 2) Add 2.0MPa nitrogen and conduct an airtightness test for 30 minutes. The test is qualified if the pressure drop is no more than 0.1MPa within 30 minutes.

[0093] 3) Add nitrogen with a space velocity of 4h -1 , and start the stirrer at a stirring rate of 400 rpm, raise the temperature to 186°C, and maintain the pressure at 1.0 MPa.

[0094] 4) Switch to air at 186℃, air speed is 4h -1 , keep the temperature constant and react for 120 minutes.

[0095] 5) After the reaction is complete, switch to nitrogen again, cool to room temperature, depressurize the reactor to normal pressure, vacuum filter the oxidation product, wash the filtered solid with 1000 ml of pure water, and then continue to filter the washed solid. The obtained solid is dried in an oven at 130° C. for 8 h, cooled to room temperature in a dryer, and the solid sample is analyzed for organic impurities and metal impurities.

[0096] Infrared online analysis of the tail gas revealed that the tail oxygen content was controlled between 3 and 6 wt%, and the CO2 content was controlled between 1.0 and 1.5 wt%. The catalyst formulation is shown in Table 1, and the results of the major impurity analysis of the product are shown in Table 2. The catalyst of this comparative example is equivalent to the composition of existing conventional catalysts. As shown in Table 2, the product exhibits low selectivity and high levels of metallic Co and Mn impurities, impacting product quality.

[0097] [Comparative Example 2]

[0098] The reaction was carried out in a 1000 ml titanium autoclave equipped with a magnetic stirrer, gas delivery line, reflux condenser, thermocouple, and rupture disc. The stirring speed was 400 rpm and the reaction was heated by circulating hot oil. The reaction steps were as follows:

[0099] 1) Weigh 80g of p-xylene, 400g of acetic acid, 20g of metal acetate (based on the entire solution, containing 500ppmwCo 2+ 、250ppmw Mn 2+ 、15ppmwZr 4+ ), and 0.44 g of 1,1,2,2-tetrabromoethane (800 ppmw of bromine based on the entire solution) were mixed evenly and added into the autoclave, which was then sealed.

[0100] 2) Add 2.0MPa nitrogen and conduct an airtightness test for 30 minutes. The test is qualified if the pressure drop is no more than 0.1MPa within 30 minutes.

[0101] 3) Add nitrogen with a space velocity of 4h -1 , and start the stirrer at a stirring rate of 400 rpm, raise the temperature to 186°C, and maintain the pressure at 1.0 MPa.

[0102] 4) Switch to air at 186℃, air velocity is 4h -1 , keep the temperature constant and react for 120 minutes.

[0103] 5) After the reaction is complete, switch to nitrogen again, cool to room temperature, depressurize the reactor to normal pressure, vacuum filter the oxidation product, wash the filtered solid with 1000 ml of pure water, and then continue to filter the washed solid. The obtained solid is dried in an oven at 130° C. for 8 h, cooled to room temperature in a dryer, and the solid sample is analyzed for organic impurities and metal impurities.

[0104] The tail gas was analyzed online using infrared, and the tail oxygen content was controlled between 3 and 6 wt%, and the CO2 content was controlled between 1.0 and 1.5 wt%. The catalyst formula is shown in Table 1, and the analysis results of the main impurities in the product are shown in Table 2.

[0105] [Comparative Example 3]

[0106] The reaction was carried out in a 1000 ml titanium autoclave equipped with a magnetic stirrer, gas delivery line, reflux condenser, thermocouple, and rupture disc. The stirring speed was 400 rpm and the reaction was heated by circulating hot oil. The reaction steps were as follows:

[0107] 1) Weigh 80g of p-xylene, 400g of acetic acid, 20g of metal acetate (based on the entire solution, containing 500ppmwCo 2+ 、250ppmw Mn 2+ ), 0.44 g of 1,1,2,2-tetrabromoethane (the bromine content is 800 ppmw based on the entire solution), and 0.10 g of potassium sodium tartrate were mixed evenly and added into the autoclave, which was then sealed.

[0108] 2) Add 2.0MPa nitrogen and conduct an airtightness test for 30 minutes. The test is qualified if the pressure drop is no more than 0.1MPa within 30 minutes.

[0109] 3) Add nitrogen with a space velocity of 4h -1 , and start the stirrer at a stirring rate of 400 rpm, raise the temperature to 186°C, and maintain the pressure at 1.0 MPa.

[0110] 4) Switch to air at 186℃, air velocity is 4h -1 , keep the temperature constant and react for 120 minutes.

[0111] 5) After the reaction is complete, switch to nitrogen again, cool to room temperature, depressurize the reactor to normal pressure, vacuum filter the oxidation product, wash the filtered solid with 1000 ml of pure water, and then continue to filter the washed solid. The obtained solid is dried in an oven at 130° C. for 8 h, cooled to room temperature in a dryer, and the solid sample is analyzed for organic impurities and metal impurities.

[0112] The tail gas was analyzed online using infrared, and the tail oxygen content was controlled between 3 and 6 wt%, and the CO2 content was controlled between 1.0 and 1.5 wt%. The catalyst formula is shown in Table 1, and the analysis results of the main impurities in the product are shown in Table 2.

[0113] Table 1

[0114]

[0115] Table 2

[0116]

[0117] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation of the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein. On the contrary, the present invention can be extended to all other methods and applications with the same function.

Claims

1. A catalyst for producing aromatic polycarboxylic acids by liquid phase oxidation, the catalyst comprising Co salt, Mn salt, IVB group salt, hydroxycarboxylate, and bromine-containing compound; in terms of weight, Co:Mn:IVB group element:hydroxycarboxylate:Br is 500:(200-300):(5-20):(10-50):(500-2000).

2. The catalyst according to claim 1, characterized in that The Co salt is cobalt acetate.

3. The catalyst according to claim 1, characterized in that The Mn salt is manganese acetate.

4. The catalyst according to claim 1, characterized in that The Group IVB salt is at least one of zirconium acetate or hafnium acetate.

5. The catalyst according to claim 1, characterized in that The hydroxycarboxylate is at least one of tartrate, heptanoate, gluconate and alginate.

6. The catalyst according to claim 1, characterized in that The bromine-containing compound is selected from at least one of inorganic bromides and brominated hydrocarbons.

7. The catalyst according to claim 6, characterized in that The inorganic bromide is selected from hydrogen bromide or alkali metal bromide.

8. The catalyst according to claim 6, characterized in that The brominated hydrocarbon is selected from at least one of tetrabromoethane, tetrabromopropane and tetrabromobutane.

9. A method for producing aromatic polycarboxylic acids by liquid phase oxidation, the method comprising reacting polyalkyl-substituted aromatic hydrocarbons with an oxidant in the presence of a catalyst as claimed in any one of claims 1 to 8 using acetic acid as a solvent to obtain aromatic polycarboxylic acids.

10. The method according to claim 1, characterized in that The aromatic hydrocarbon is benzene or naphthalene; the oxidant is a gas containing elemental oxygen; preferably, the reaction temperature is 160-250°C; preferably, the reaction pressure is 0.8-2.0 MPa; preferably, the reaction time is 1-5 hours; preferably, the mass ratio of the polyalkyl substituted aromatic hydrocarbon, the solvent, and the catalyst in terms of Co is 1:(2-10):(1×10 -4 ~1×10 -3 ).

Citation Information

Patent Citations

  • Process for preparing aromatic polycarboxylic acid by liquid phase oxidation

    US7985875B2

  • Recovery of aromatic carboxylic acids and oxidation catalyst

    CN102199082A

  • Catalyst for preparing aromatic polycarboxylic acid through liquid phase oxidation

    CN107774315A

  • Method for reactivating a group VIII noble metal catalyst for use in the purification of crude terephthalic acid

    US4808751A

  • Production of polycarboxylic acids with hafnium-activated cobalt catalyst

    US5112992A